A comparison of load-distributive path routing and shortest path routing in wireless ad hoc networks - Habib, I. (IEEE Computer Society, 2014)
Wireless ad-hoc networks are collections of wireless nodes having no predefined infrastructure. Most of the existing routing protocols for wireless ad-hoc networks use the shortest path or minimum distance path to the destination. However, the shortest path routing does not provide a good balance of the traffic load among all nodes. When many users utilize the shortest paths, some nodes become highly congested and become what is known as hotspots. These hotspots degrade the performance of wireless ad-hoc networks by creating long queuing and contention delays. This paper investigates the effects of shortest path routing on the network by varying different network parameters. A load distributed path routing is also proposed to enhance the performance of shortest path routing. Matlab simulations show that the load distributive routing provides 35 and 44 less contentions in a 20-node and 30-node network respectively, when compared to shortest path routing. Â© 2014 IEEE.